The Tonoplastic Inositol Transporter INT1 From Arabidopsis thaliana Impacts Cell Elongation in a Sucrose-Dependent Way - Strobl, Sabrina Maria; Kischka, Dominik; Heilmann, Ingo; Mouille, Grégory; Schneider, Sabine (Frontiers in Plant Science, 2018)
The tonoplastic inositol transporter INT1 is the only known transport protein in Arabidopsis that facilitates myo-inositol import from the vacuole into the cytoplasm. Impairment of the release of vacuolar inositol by knockout of INT1 results in a severe inhibition of cell elongation in roots as well as in etiolated hypocotyls. Importantly, a more strongly reduced cell elongation was observed when sucrose was supplied in the growth medium, and this sucrose-dependent effect can be complemented by the addition of exogenous myo-inositol. Comparing int1 mutants (defective in transport) with mutants defective in myo-inositol biosynthesis (mips1 mutants) revealed that the sucrose-induced inhibition in cell elongation does not just depend on inositol depletion. Secondary effects as observed for altered availability of inositol in biosynthesis mutants, as disturbed membrane turnover, alterations in PIN protein localization or alterations in inositol-derived signaling molecules could be ruled out to be responsible for impairing the cell elongation in int1 mutants. Although the molecular mechanism remains to be elucidated, our data implicate a crucial role of INT1-transported myo-inositol in regulating cell elongation in a sucrose-dependent manner and underline recent reports of regulatory roles for sucrose and other carbohydrate intermediates as metabolic semaphores.